Relevansi dan Aktualisasi Teologi dalam Kehidupan Sosial menurut Harun Nasution - Muhammad Arifin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
This article analyses relevancy and actualization of theology, which is introduced by Harun Nasution, with the social life. Further, it will be drawn to Indonesia community life in order to result a thought frame that shapes scientific and logic attitude without leaving the basic value of Islamic teachings. This research finds that the Harun Nasution concept on Rational Theology has relevancy to Indonesia community life, in which its relevancy values is closer to modern society life. By having such concept, society is expected to become critics to social phenomena that they encounter on daily basis.